(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
Purpose of the Study: This research addresses a relatively new field; its primary objective is to determine whether the use of strategic momentum in productive organizations leads to the enhancement of organizational brilliance. Furthermore, the study aims to focus on modern strategic management approaches—including strategic momentum—and clarify their pivotal role in creating a comprehensive and integrated environment that fosters growth and differentiation, thereby advancing the industrial sector through the introduction of the concept of organizational brilliance. Methodology: A sample was selected from employees at the Men’s Garments Factory in Al-Najaf Al-Ashraf. A questionnaire consisting of 22 questions was distributed to employees, including unit and division managers, department heads, accountants, and production staff. A total of 93 completed forms were collected. Key Findings: The study results revealed a significant and meaningful impact of strategic momentum on organizational brilliance. According to the findings, the path coefficient of the explanatory variable (strategic momentum) showed strong influence on the responsive variable (organizational brilliance), indicating that strategic momentum plays a powerful role in organizing and enhancing employee brilliance within the industrial sector (the factory under study). Applications of the Study: Strategic momentum can play a critical role in enhancing industrial performance by creating a comprehensive and integrated environment that promotes leadership brilliance, service excellence, innovation, knowledge, efficiency, and financial inclusion. This contributes to elevating the status of the factory under study. Productive factories that adopt strategic momentum can remain at the forefront of the curve, deliver superior services to their customers, maintain market share, and contribute to the sustainable and inclusive development of the national economy.